Perhitungan Pasang Surut Sebagai Data Pendukung Dalam Penataan Kawasan Daerah Pesisir Teluk Betung Bandar Lampung. - Yuda Romdania (UNIVERSITAS LAMPUNG, 2010)
To ensure continuity of economic activity in particular and development in a broad sense in this area, the development of various facilities which are expected to support economic activity is much-needed. Therefore we need a spatial development that is community based by rearranging the relevant regional spatial planning by involving the community in the spatial planning process.As a coastal area, tidal factor wil affect spatial planning in Teluk Betung Bandarlampung coastal area. Tidal data will be used in structuring the analysis of coastal areas as a primary or secondary data.The type of tides in the coast area of Teluk Betung, Bandar Lampung is semi-diurnal type. This implies that the region experienced double-tide and low tide twice daily. Within one month, there are two occurance of high tide (spring tide) and low tide (neap tide).Tides in Teluk Betung Bandar Lampung coast are has a range (tidal range) of 114 cm (= 119 cm - 5 cm recording on signs), or has an amplitude of about 57 cm.